Decolonizing diakonia: from servanthood to companionship - Cho, Hyuk (Studien zur interkulturellen Geschichte des Christentums, 2025)
"The traditional concept of diakonia centres on servanthood and humble service, leading to inconsistencies in mission practice and necessitating revision. If diakonia continues to be defined as servanthood, it risks objectifying people, excluding them from being subjects of mission, failing to learn from others, and mystifying the power of domination. Since diakonia has been essential to the mission of the church from its early days, its interpretation significantly influences the church's self-understanding, current mission and relationships with others. Decolonizing Diakonia explores these issues by examining the Bible, historical developments, theology of service, and Katherine Hockin's companionship. This book discovers new language, images, and practices for diakonia that align with postcolonial contexts, emphasizing just, respectful, and compassionate relationships among those participating in God's mission today. Hockin's concept of diakonia as companionship is a fitting idea and practice for our mission. Her notion of companionship is inclusive, allowing everyone to participate in God's mission as equals regardless of their status or privilege within society's power structures. This companionship transforms the power dynamics from being for others into with each other. Decolonizing Diakonia contributes to a deeper understanding of the importance of intercultural and postcolonial hermeneutics as a critique of power and decolonizing mission practice"-- Provided by publisher